DEVELOPMENT OF INDEPENDENT WORK SKILLS OF PRIMARY CLASS STUDENTS - Dilfuza MELIEVA (Scholar Express Journal, 2024)
This article shows ways to widely use modern educational technologies based on an innovative approach to teach primary school students to think independently, highlights the importance and advantages of the innovative approach.
Keywords: Activity; independent thinking; thinking